- Thread starter
- #1

#### karush

##### Well-known member

- Jan 31, 2012

- 2,928

$y''+2y'=3x$

$y_p = \frac{3}{4}x^2 - \frac{3}{4}x$,

$y(0)=y'(0)=0$

$r^2 + 2r = 0$

$r(r-2)=0$

$r=0$

$r=2$

more steps...

$\textrm{mml final answer}$

$y=\frac{3}{8}\left(1-e^{-2x}\right)+\frac{3}{4}x^2 - \frac{3}{4}x$

$y_p = \frac{3}{4}x^2 - \frac{3}{4}x$,

$y(0)=y'(0)=0$

$r^2 + 2r = 0$

$r(r-2)=0$

$r=0$

$r=2$

more steps...

$\textrm{mml final answer}$

$y=\frac{3}{8}\left(1-e^{-2x}\right)+\frac{3}{4}x^2 - \frac{3}{4}x$

Last edited: